(untitled) (Bangladesh Journal of Urology, 2020)
Background: Several different modalities are available for ureteral stone fragmentation. From them pneumatic and holmium: yttrium-aluminum-garnet (Ho: YAG) lithotripsy have supportive outcomes. Aims: To see the outcome of lower ureteric stone fragmentation by laser in comparison with pneumatic lithotripsy. Methods: The prospective clinical study was conducted during the period from July 2012 to June 2014 in Dhaka Medical College Hospital. From the patient admitted in Dhaka medical college hospital a total of 60 patient were selected using purposive sampling methods. Selected patients were numbered chronologically and odd number group as group A (laser lithotripsy) and even number group B (pneumatic lithtripsy). Cystoscopy followed by ureterescopy with the help of guide wire was done and stone fragmentation done by either laser lithotripsy (done in general operation theatre in Dhaka Medical College Hospital) or pneumatic lithotripsy (done in Urology operation theatre in Dhaka Medical College Hospital). Collected data were processed and analyzed using computer software SPSS (statistical package for social science), version-18. Un-pair t-test, chisquare test and Fishers Exact probability test were used to analyze the data. The findings of the study showed age and sex are almost identically distributed in both groups. Results: The mean age of group A and group- B were 35.63±11.66 and 38.90±11.21 years respectively. A male predominance was observed in both groups with 70% male in group- A and 53.3% in group-B. Stone size was also observed identically in both groups. 43% of stone are larger than 10mm in group- A and 47% stone are larger than 10mm. None of other baseline variable found very between groups. Immediate stone clearance was much higher in group-A (96.7%) then that in group- B (80%). Although both the groups demonstrated 100% clearance after 1 month. Immediate complications were higher in group B then those of group- A. Ureteral perforation in group B was found 6.7% as opposed to none in group-A. Fever in group A (6.7%) was observed to be more than 3 times higher than in group- B (23.3%). Comparison of complications after 1 and 3 months shows some differences (higher in group-B) but that is not significant. Ureteral stricture developed in 3 patients in group- B compared to nil in group- A. More than 90% of patients of group-A were released from the hospital within 3 days after operation, in contrast about 40% in group-B left the hospital within 3 days. Conclusion: So, laser lithotripsy is better option for the management of lower ureteric stone by using semi rigid ureteroscope, in term of stone migration, rate of stone fragmentation and clearance, operation time, hospital stay and complication. Bangladesh Journal of Urology, Vol. 23, No. 2, July 2020 p.169-175